Mirror for man: a survey of human behavior and social attitudes - Kluckhohn, Clyde (Greenwich, Conn. : Fawcett Publications, 1944)
Includes bibliographical references (p. 232-235) and index.
Keywords: Anthropology; United States--Civilization.